Molecular Docking and Molecular Dynamics - Stefaniu, Amalia (IntechOpen, 2019)
This book clearly explains the principles of in silico tools of molecular docking and molecular dynamics. It provides examples of algorithms and procedures proposed by different software programs for visualizing and identifying potential interactions in complexes of biochemical interest. The book is structured in six chapters, each of which discusses different molecular simulation methodologies and provides concrete examples of complexes interactions. In each chapter authors give an overview of the treated subject, a description of the methodologies used, and a discussion of the results. The authors describe computational ways to achieve a rational design of bioactive compounds with various therapeutic applications, including antitumoral agents, antitubercular drugs, nonsteroidal anti-inflammatory drugs, and radiopharmaceuticals.